Determinant Employee Productivity and Organization Sustainability: Analysis Performance Appraisals, Evaluation Performance, Competence Employee and Motivation - Emmy Junianti; Juniawan Mandala Putra; Ratna Tri Hari Safariningsih; Agus Dharmanto; Didin Sjarifudin (Formosa Journal of Sustainable Research, 2023)
The purpose of this study is to measure organizational sustainability with several constructs that are considered supporters, including performance appraisals, performance evaluations, employee competence, and motivation. The research method of this article uses a literature review study, Literature Study is a way to solve problems by tracing the sources of writing that have been made before.  The novelty of this article is the framework formed from the reference to previous international journal articles, findings of significance, and insignificance between variables. The gap in this study is described in a complete research result description and supported by previous articles